PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA BPJS SEKTOR MANDIRI: ANALISIS JALUR DAN REGRESI BERGANDA PADA BPJS KETENAGAKERJAAN CABANG SERANG, PROVINSI BANTEN: Service Quality and Its Impact on Independent BPJS Participants’ Satisfaction: A Path Analysis and Multiple Regression Study at BPJS Employment, Serang Branch, Banten Province - Sudarwoto Sudarwoto; Erna Erna; Agus Hendarto (Universitas Wiralodra, 2025)
Service quality is a crucial factor determining participant satisfaction with social security institutions. This study aims to examine the direct and indirect influence of service quality on participant satisfaction of the Independent Sector BPJS Ketenagakerjaan (BPJS Ketenagakerjaan) at the Serang Branch Office, Banten Province. The analysis was conducted using multiple regression and path analysis. Various indicators of participant dissatisfaction—such as lengthy service processes, unclear information provided, and low staff responsiveness—demonstrate the need for an empirical assessment of service quality elements based on the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. This study employed a quantitative approach, involving 100 respondents from the independent sector selected through purposive sampling. The research instrument was a structured questionnaire that was tested for validity and reliability to ensure data accuracy and consistency. The results of the multiple regression analysis indicate that each dimension of service quality has a positive and significant influence on participant satisfaction, both individually and collectively. The path analysis found that the dimensions of reliability and responsiveness had the strongest direct contribution to satisfaction. Meanwhile, the empathy dimension has an indirect influence through participant perceptions of service assurance. The coefficient of determination indicates that service quality explains most of the variation in participant satisfaction, with the remainder influenced by other factors such as perceptions of service costs, the organizational culture of the provider, and participants' previous experiences receiving services. Overall, this study confirms that improving overall service quality is a strategic step to strengthen the satisfaction and trust of BPJS Ketenagakerjaan participants in the independent sector. Recommendations resulting from this study include improving the effectiveness of the service information system, developing staff competencies, and establishing consistent and easily accessible service time standards for participants.